PERKEMBANGAN PERGURUAN PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE (PSHT) DI KENAGARIAN LUBUAK GADANG KECAMATAN SANGIR KABUPATEN SOLOK SELATAN (1991-2010). - Abadi, Yuriko; Erawati, Meri; Zulfa, Zulfa (Pendidikan Sejarah, 2014)
The development of Institution Pencak Silat Persaudaraan Setia Hati Terate (PSHT) in Kenagarian Lubuak Gadang Kecamatan Sangir Kabupaten Solok Selatan (1991-2010). History Education of Program. STKIP PGRI West Sumatra. Padang 2014. This thesis discuss about the development of Institution the Pencak Silat Persaudaraan Setia Hati Terate (PSHT) in Kenagarian Lubuak Gadang Kecamatan Sangir Kabupaten Solok Selatan (1991-2010). To facilitate this research, the problem can be formulated as follows: (1) How does the beginning of Institution Pencak SilatÂ PSHT in Kenagarian Lubuak Gadang (2) How does the development of Institution Pencak Silat PSHT in Kenagarian Lubuak Gadang. (3) How does the impact of the establishment PSHT on the existence of the Java in Kenagarian Lubuak, Sangir. The purposes of this study are (1) to describe the beginning of establishment PSHT (2) To describe the historical development of Institution Pencak Silat PSHT. (3) To describes the impact of the establishment PSHT on the existence of the Java in Kenagarian Lubuak Gadang, Sangir. The method used in this study is the historical method. The method consists of the following four stages: (1) Heuristic is a collect the data, looking for the source and concludes to library study and interviews. (2) Criticism source, in order to obtain the facts of history. (3) Interpretation, the obtained data analyzed and interpreted with connecting and comparing the observed facts so the fact that ready to be served. (4) Historiography, writing in the form of scientific papers after collect the data and facts that really accurate and valid then write in the form of a thesis.This study describes the results : ( 1 ) The beginning of establishment PSHT in Kenagarian Lubuak Gadang is because request of citizen of Kenagaian Lubuak Gadang, Sangir and because there is an intensive communication between the members of PSHT in Java with members of PSHT who migrated to West Sumatra , especially in Kenagarian Lubuak Sangir, solok selatan. (2) The development of PSHT start from development of the Organizational Structure which structured well, and development of leaders are always changing but still make PSHT always evolving and achievement, and then the number of its graduateâs students is always evolving every endorsement convening every 2 years once. (3) The impact of the existence of the Java PSHT in Kecamatan Sangir is the creation of a sense of brotherhood among the Minang with Java, not even a conflict between the two sides.